2015
DOI: 10.1002/mnfr.201500338
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of oxidative stress in brain of ovariectomized rats with omega-3 and lipoic acid

Abstract: These results suggest that the antioxidant response to omega-3 varies in different tissues, and in this study DHA treatment had a prooxidant effect in the brain. Lipoic acid treatment, on the other hand, had a protective effect, reducing markers of oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…The present study also indicated that DHA-rich fish oil can reduce lipid peroxidation and hence can protect the brain against stress-induced oxidative stress. This finding is parallel to other studies investigating the effect of omega-3 fatty acids on the brain 28 and also on other organs 29 However, the effect of omega-3 fatty acids on lipid peroxidation is still inconclusive as a number of studies have shown that it can increase lipid peroxidation in many organs 30 , 31 while other studies indicated that it does no influence lipid peroxidation at all. 32 The extent of lipid peroxidation may be region dependent.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present study also indicated that DHA-rich fish oil can reduce lipid peroxidation and hence can protect the brain against stress-induced oxidative stress. This finding is parallel to other studies investigating the effect of omega-3 fatty acids on the brain 28 and also on other organs 29 However, the effect of omega-3 fatty acids on lipid peroxidation is still inconclusive as a number of studies have shown that it can increase lipid peroxidation in many organs 30 , 31 while other studies indicated that it does no influence lipid peroxidation at all. 32 The extent of lipid peroxidation may be region dependent.…”
Section: Discussionsupporting
confidence: 80%
“… 32 The extent of lipid peroxidation may be region dependent. 31 It has been shown the amount of lipid peroxidation decreased in some regions of the brain but remains unchanged in some other regions following omega-3 fatty acids supplementation. 33 It has also been suggested that whether omega-3 fatty acids exhibit antioxidant or pro-oxidant activity in the mammalian brain depends on the experimental protocols and the dosage of omega-3 fatty acids administered.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed that the theoretical propensity for fatty acid oxidation is proportional to its degree of unsaturation, and in this regard, supplementation with highly unsaturated PUFAs has been associated with increased oxidative damage in animals and humans. [62][63][64][65] We suggest that the antioxidant response to ω-3 varies by organ and tissue, and in the current study, 66 DHA supplementation exhibited antioxidant effects in the brain. Emerging epidemiological and molecular genetic evidence further suggests that dietary intake of lipids such as DHA and high-fat cholesterol (HF-C) are active regulators of oxidative processes that can prevent or support neurodegeneration in brain cells, respectively.…”
Section: Papermentioning
confidence: 82%
“…Ovariectomy increases the consumption of ascorbic acid and other antioxidant enzymes and proteins [22]. The glutathione system plays an important role in providing a primary defense mechanism for the elimination of reactive oxygen species in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus and prefrontal cortex are considered as very susceptible to oxidative stress and implicated in anxiety, depression and cognitive impairments [21]. Low estrogen levels are also associated with increased oxidative stress and increased free radicals in the brain [7,22]. It has been proven that oxidative stress plays a significant role in the pathogenesis of anxiety and depression by causing neuronal degeneration in the brain [12].…”
Section: Discussionmentioning
confidence: 99%